Canadian Association of Gastroenterology Policy on the Application for, and Implementation of, Clinical Practice Guidelines. Issue 9 (2014) - Singh, Harminder; Leontiadis, Grigorios I; Hookey, Lawrence; Enns, Robert; Bistritz, Lana; Rioux, Louis-Charles; Hope, Louise; Sinclair, Paul
Abstract : An important mandate of the Canadian Association of Gastroenterology (CAG), as documented in the Association's governance policies, is to optimize the care of patients with digestive disorders. Clinical practice guidelines are one means of achieving this goal. The benefits of timely, high-quality and evidenced-based recommendations include: Enhancing the professional development of clinical members through education and dissemination of synthesized clinical research; Improving patient care provided by members by providing focus on quality and evidence; Creating legislative environments that favour effective clinical practice; Enhancing the clinical care provided to patients with digestive disease by nongastroenterologists; and Identifying areas that require further information or research to improve clinical care. The present document provides the foundation required to ensure that clinical practice guidelines produced by the CAG are necessary, appropriate, credible and applicable. These recommendations should be adhered to as closely as possible to obtain CAG endorsement.